If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -2x + -7 = x + 26 Reorder the terms: -7 + -2x = x + 26 Reorder the terms: -7 + -2x = 26 + x Solving -7 + -2x = 26 + x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. -7 + -2x + -1x = 26 + x + -1x Combine like terms: -2x + -1x = -3x -7 + -3x = 26 + x + -1x Combine like terms: x + -1x = 0 -7 + -3x = 26 + 0 -7 + -3x = 26 Add '7' to each side of the equation. -7 + 7 + -3x = 26 + 7 Combine like terms: -7 + 7 = 0 0 + -3x = 26 + 7 -3x = 26 + 7 Combine like terms: 26 + 7 = 33 -3x = 33 Divide each side by '-3'. x = -11 Simplifying x = -11
| H(x)=2x^2-12x+17 | | Y=(x-5)(2x+3) | | -a-7=3a+17 | | -56=8/9(4-x) | | 20+-1=95 | | 10=2(k+2) | | -12b^2+2ab+a-6b=0 | | 65(x-2)=2(9-2x) | | 4t=-2 | | 3x+4r+2wq+1=4x+2w | | 3u+1=4u | | y=m+b | | 10(v+1)-2v=4(2v+3)-18 | | [(7m^2+5m-10)-(5m^2+3m+3)]-(m^2+m+2)= | | 1/2(3x-7)=4 | | 19-4p=a | | -6(a-3)=-3(a+8) | | V/3.4r(2) | | 4b/2-3=11-b | | 10+18=-v+8v | | 7x+7=4x+2 | | 4.75w=76 | | 1+5r=1-6r | | Y-6=4/3(x-14) | | 2x-4-3z=1 | | 4(2t-1)+3t=8-1 | | 23x-13y=1 | | 109=-7x-3 | | (-1+3i)(2-i)= | | -9+16=-4x-6x | | -12+-4x+5=4x+12 | | 3.65y=73 |